2013
DOI: 10.1080/07391102.2013.817954
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the cavity-binding site of three bacterial multicopper oxidases upon complex stabilization: interactional profile and electron transference pathways

Abstract: Previous studies have shown that multicopper oxidases (MCOs) oxidize organic and inorganic compounds through oxidation-reduction reactions in which three structurally and functionally arranged copper centers coordinate the uptake of an electron from a reduced substrate. Structural comparisons among three bacterial MCOs, with high structural homology and available three-dimensional information, reveal that the primary structural differences between these MCOs are located near the mononuclear copper center (T1Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…low affinity. Interestingly, MD simulations of Tt Lac and analogous hairpin-deletant earlier demonstrated a similar manner of ABTS docking to both molecules despite hairpin absence thus confirming our experimental observations. , …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…low affinity. Interestingly, MD simulations of Tt Lac and analogous hairpin-deletant earlier demonstrated a similar manner of ABTS docking to both molecules despite hairpin absence thus confirming our experimental observations. , …”
Section: Resultssupporting
confidence: 86%
“…Interestingly, MD simulations of Tt Lac and analogous hairpin-deletant earlier demonstrated a similar manner of ABTS docking to both molecules despite hairpin absence thus confirming our experimental observations. 54,55 In agreement with the solution assay, the Δ-hairpin Lac behaved similarly to the wild type when immobilized on Neg-CNTs or Pos-CNTs (Figure S16). On Neg-CNTs no DET process could be observed, and a catalytic wave similar to the WT was obtained in the presence of Cu 2+ .…”
Section: ■ Experimental Sectionsupporting
confidence: 74%
“…The carbon nanofibers used in the current work present a hydrophobic surface, suggesting that hydrophobic interaction should also play a key role in the efficient electrical wiring of the enzyme [35]. This is not unexpected as it was demonstrated that substrate-enzyme complex was mainly driven by hydrophobic interactions [43]. The mutants were then adsorbed on the same carbon nanofiber-modified electrode.…”
Section: Effect Of T1 Cu Site Mutation On Onset Potentials For O2 Reductionsupporting
confidence: 55%
“…Both cavities are comparable to those in other prokaryotic MCOs (Figure S3): cavity A is closer to the substrate-binding site in Bacillus subtilis CotA and cavity B to the substrate-binding site in E. coli CueO and Thermus thermophilus Tth multicopper oxidases …”
Section: Resultsmentioning
confidence: 99%